Analysis of Intraseasonal Oscillation Characteristics of Arctic Summer Sea Ice. Issue 5 (28th February 2020) - Qian, Shimeng; Zhang, Lujun; Yang, Ben; Huang, Anning; Zhang, Yaocun
Abstract: This study investigates the intraseasonal variations of the Arctic sea ice concentration (SIC) based on daily data band‐passed for 20–80 days. Results show that the areas with strong intraseasonal signal of SIC move northward and then southward before and after the Arctic summer (i.e., from August to October), respectively, and the signal reaches its maximum intensity in summer. Power spectrum analyses indicate that the SIC over the region bounded by 0–180°E and 70–80°N (60–180°W and 70–80°N) in summer exhibits remarkable intraseasonal variation with a dominant period of 40–60 days (two typical periods of 40–60 and 70–80 days). These two kinds of oscillations move eastward along the Arctic marginal sea. In addition, the intensity of SIC intraseasonal oscillation has an apparent interdecadal change that is closely related to the decrease of Arctic sea ice extent. Plain Language Summary: Daily records over the past 40 years indicate that the Arctic sea ice varies quickly on intraseasonal time scales. The area with strong intraseasonal variation of sea ice moves northward when summer is approaching and southward after summer. During the Arctic summer, the SIC intraseasonal oscillation signal with two dominant periods of 40–60 and 70–80 days propagates eastward along the Arctic marginal sea. In respond to the warming climate, the sharp reduction in the Arctic sea ice extent has caused an evident northward shift of the location with strong intraseasonal variation. Key Points: Sea ice in the Arctic marginal sea has intraseasonal oscillation with periods of 40–60 and 70–80 days The intraseasonal signals move eastward along the Arctic marginal sea The intensity of the intraseasonal oscillation of sea ice has a interdecadal change due to the decrease of Arctic sea ice area